Diagnosing active tuberculosis in people living with HIV: an ongoing challenge. Issue 1 (January 2019) - MacLean, Emily; Saravu, Kavitha; Pai, Madhukar
Abstract : Purpose of review: Diagnosis of tuberculosis (TB) in people living with HIV (PLHIV) remains a challenge, despite it being the most common comorbidity in this group. In this review, we provide an overview of tests for active TB, and their diagnostic performance in PLHIV. Recent findings: New and updated diagnostic tests have better performance than traditional bacterial culture or smear microscopy in PLHIV. Recent developments in molecular tests have improved the sensitivity at which TB and drug susceptibility can be detected in PLHIV. Notably, the updated Xpert Ultra test can detect HIV-associated TB with high sensitivity, and a rapid lateral flow lipoarabinomannan-based assay has been shown to reduce TB-related mortality in hospitalized PLHIV. New directions in drug-susceptibility testing are being pursued, such as next-generation sequencing and line probe assays, but more evaluation in PLHIV is needed. There is growing understanding of subclinical TB, but methods to detect this type of TB are inadequate. Summary: As diagnosis is the weakest link in the TB care cascade, newer more accurate TB tests must be scaled up and fully integrated into existing healthcare systems. Drug-susceptibility testing must become universal to ensure appropriate treatment regimens are prescribed, allowing TB clearance and inhibiting development of antimicrobial resistance.